TEKNIK DAN IDEOLOGI PENERJEMAHAN DI WORDPRESS - Raja Rachmawati (Madah: Jurnal Bahasa dan Sastra, 2016)
The topic of this article is about translation in blog, especially WordPress. This research aims at identifying the translation techniques and ideology in translating blog terms which are applied by Google Inc in WordPress. This method is descriptive qualitative. The data of this research is blog terms that exist in WordPress in forms of words, phrases, clauses and sentences. The technique used in this research is writing technique. The result of the research shows that there are 47 words, 12 phrases, 41 sentences blog terms in WordPress in English. There are six techniques found in the data, namely 1) borrowing technique, 2) calque technique,3) literal technique, 4) reduction technique, 5) transpotition`technique,and 6) the comibnation of some techniques. The ideology of the translation mostly found is foreignization.